2020
DOI: 10.1152/ajpcell.00055.2020
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HOXA9 after skeletal muscle denervation and reinnervation

Abstract: Homeobox A9 (HOXA9), the expression of which is promoted by mixed lineage leukemia 1 (MLL1) and WD-40 repeat protein 5 (WDR5), is a homeodomain-containing transcription factor that plays an essential role in regulating stem cell activity. HOXA9 has been found to inhibit skeletal muscle regeneration and delay recovery after muscle wounding in aged mice, but little is known about its role in denervated/reinnervated muscles. We performed detailed time-dependent expression analyses of HOXA9 and its promoters, MLL1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Overexpression of HOXA 9 significantly promoted the mRNA expression of BAD and BAX genes, reduced the expression of BCL 2 gene, and increased the apoptosis rate. Moreover, previous studies showed that HOXA 9 accelerated the apoptosis process of primary muscle satellite cells by affecting atrophic Signaling pathways [ 50 ] and negatively regulated downstream anti-apoptosis and autophagy-promoting genes (including BCL-XL , ULK 1, ATG 3 and ATG 12) of NF-κB to promote the apoptosis of skin squamous cell carcinoma (cSCC) cells and inhibit autophagy [ 51 ]. This meant HOXA 9 promoted cells apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of HOXA 9 significantly promoted the mRNA expression of BAD and BAX genes, reduced the expression of BCL 2 gene, and increased the apoptosis rate. Moreover, previous studies showed that HOXA 9 accelerated the apoptosis process of primary muscle satellite cells by affecting atrophic Signaling pathways [ 50 ] and negatively regulated downstream anti-apoptosis and autophagy-promoting genes (including BCL-XL , ULK 1, ATG 3 and ATG 12) of NF-κB to promote the apoptosis of skin squamous cell carcinoma (cSCC) cells and inhibit autophagy [ 51 ]. This meant HOXA 9 promoted cells apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies report that HOXA9 is involved in cell proliferation [ 38 40 ]. One study demonstrated that HOXA9 may promote denervated muscle atrophy by strongly upregulating MLL1 and WDR5 expression and inhibiting myogenic differentiation [ 23 ]. Furthermore, HOXA9 deletion improves satellite cell function and muscle regeneration in aged mice, whereas HOXA9 overexpression mimics age-associated defects in satellite cells from young mice, which can be rescued by inhibiting HOXA9-targeted developmental pathways.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism involved in circRNAFUT10 and miR-365a-3p interactions needs to be further studied. In addition, Homeobox protein Hox-A9 (HOXA9) is related to denervated muscle atrophy [ 23 ], and inhibiting HOXA9 improved SkMSCs function and muscle regeneration in aged mice [ 24 ]. Similar to circRNA FUT10, bioinformatic analysis predicted the presence of binding sites for miR-365a-3p in the 3′-untranslated regions (UTRs) of HOXA9 mRNA.…”
Section: Introductionmentioning
confidence: 99%
“…HOXA9 expression is promoted by complexes composed of mixed lineage leukemia 1 (MLL1), a histone H3 lysine 4 (H3K4) methylransferase, and WD-40 repeat protein 5 (WDR5) [ 128 ]. Therefore, ruining the MLL1/WDR5 protein–protein interaction is a helpful means to indirectly target HOXA9.…”
Section: Wdr5-mll Inhibitorsmentioning
confidence: 99%